To the honorable General Assembly of the colony of Connecticut : to be holden at Hartford, on the second Thursday of May next. The memorial of the subscribers, freemen and inhabitants of said colony, humbly sheweth . (Printed by Eben. Watson, 1774)
March 10, 1774 citizens' petition to the Connecticut General Assembly, which sought the investigation of the then current schools and the use of public funding in order that the assembly might reform the abuses through the establishment and maintenance of public schools.